Pengelolaan Alokasi Dana Desa Pada Anggaran Pendapatan Dan Belanja Nagari Tahun 2021 - Asrinaldi (Sekolah Tinggi Ekonomi Syariah (STES) Manna wa Salwa, 2022)
In this research, the main issue is regarding the Effectiveness of Managing Village Fund Allocations in Nagari Pagaruyung's Revenue and Expenditure Budget. management of village fund allocations in the 2021 Nagari Revenue and Expenditure Budget. The method used is descriptive with a qualitative approach. The data collection technique used in this study was through direct interviews with Nagari Pagaruyung and documentation. Descriptive results through measurement or criteria of effectiveness that the authors apply to the real conditions that occur in the field. The research show that Nagari Pagaruyung has carried out the tasks as planned in Nagari Pagaruyung's Revenue and Expenditure Budget, and in the planning and preparation of the village fund allocation management program in Nagari Pagaruyung's Revenue and Expenditure Budget it has been effective in accordance with Permendagri Number 20 of 2018. And in managing the allocation of village funds, there are several inhibiting factors that affect the effectiveness and inefficiency of managing village fund allocations in the Nagari Pagaruyung Revenue and Expenditure Budget, namely delays in disbursing funds from the local government community participation in managing village funds in Nagari Pagaruyung.